Synthetic vs. non-synthetic sweeteners: their differential effects on gut microbiome diversity and function - Kidangathazhe, Alex; Amponsah, Theresah; Maji, Abhijit; Adams, Seidu; Chettoor, Maria; Wang, Xiuqing; Scaria, Joy (Frontiers in Microbiology, 2025)
The rising use of artificial sweeteners, favored for their zero-calorie content and superior sweetness, necessitates understanding their impact on the gut microbiome. This study examines the effects of five common artificial sweeteners—Acesulfame K, Rebaudioside A, Saccharin, Sucralose, and Xylitol—on gut microbiome diversity using minibioreactor arrays. Fecal samples from three healthy individuals were used to inoculate bioreactors that were subsequently supplemented with each sweetener. Over 35 days, microbial diversity and network composition were analyzed. Results revealed synthetic sweeteners like Sucralose and Saccharin significantly reduced microbial diversity, while non-synthetic sweeteners, particularly Rebaudioside A and Xylitol, were less disruptive. Acesulfame K increased diversity but disrupted network structure, suggesting potential long-term negative impacts on microbiome resilience. Sucralose enriched pathogenic families such as Enterobacteriaceae, whereas natural sweeteners promoted beneficial taxa like Lachnospiraceae. Random Matrix Theory (RMT) based analysis highlighted distinct microbial interaction patterns, with Acesulfame K causing persistent structural changes. Findings suggest non-synthetic sweeteners may be more favorable for gut health than synthetic ones, emphasizing cautious use, particularly for those with gut health concerns. This study enhances our understanding of artificial sweeteners’ effects on the gut microbiome, highlighting the need for further research into their long-term health implications.